2018
DOI: 10.1096/fj.201700713r
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulation of GDNF/Ret signaling in dopaminergic neurons

Abstract: 1,25(OH)D (vitamin D) appears essential for the normal development of dopaminergic neurons. Vitamin D affects dopamine synthesis and metabolism as well as expression of glial cell line-derived neurotrophic factor (GDNF), which is crucial for the survival of dopaminergic neurons. We investigated the role of vitamin D on GDNF and its receptors protooncogene tyrosine-protein kinase receptor Ret (C-Ret) and GDNF family receptor alpha 1 (GFRα1) signaling. To this end, we used a developmental vitamin D-deficient rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 57 publications
4
61
0
Order By: Relevance
“…33 Vitamin D could protect the dopamine system by modulating GDNF receptor, C-Ret, which is greatly important for cell differentiation and survival of dopaminergic neurons. 34 These studies suggested that vitamin D deficiency in fetuses or early brain development might be contributing to the etiology of tic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…33 Vitamin D could protect the dopamine system by modulating GDNF receptor, C-Ret, which is greatly important for cell differentiation and survival of dopaminergic neurons. 34 These studies suggested that vitamin D deficiency in fetuses or early brain development might be contributing to the etiology of tic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has also been related to synthesis of monoamines (serotonin, dopamine, and noradrenaline) and its steroidal features may allow it to modulate the activity of GABA‐A receptors (Bertone‐Johnson, 2009; Humble, 2010; Maguire, Ferando, Simonsen, & Mody, 2009; Marsh, Penny, & Rothschild, 2017; Panzica & Melcangi, 2008; Patrick & Ames, 2014). In addition several studies have shown that vitamin D is associated with nerve growth factor enhancement and antioxidant effects in the central nervous system (Humble, 2010; Moradi, Sohrabi, Taheri, Khodashenas, & Movahedi, 2018; Pertile, Cui, Hammond, & Eyles, 2018; Sepehrmanesh et al, 2016). It is therefore biologically plausible that vitamin D would have psychiatric applications and the possibilities are worthy of investigation (Bertone‐Johnson, 2009; Humble, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…GDNF has been shown to be an important neuroprotective factor, and increased levels of GDNF have been demonstrated after treatment with calcitriol in models of oxidative brain injury [34] and autoimmune encephalitis [35]. Treating neuronal cells with calcitriol also increases levels of c-Ret mRNA, a GDNF receptor [36]. Additionally, pups born to vitamin D-deficient dams demonstrate lower levels of GDNF [13].…”
Section: Vitamin D and The Injured Brainmentioning
confidence: 99%